Structures Congress 2012 2012
DOI: 10.1061/9780784412367.196
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Dynamic Characteristics of Reinforced Concrete Shear Wall Buildings

Abstract: Structural engineers routinely need to make assumptions about the dynamic properties (natural periods, mode shapes, and damping) of a building to simulate its response to dynamic loads, such as strong winds or earthquake ground motions. However, the assumed properties may significantly differ from those of the actual building, once it is constructed, due to differences between the idealized model and in situ conditions. The main objectives of this study are to evaluate how common models and assumptions used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…The problem lies in the fact that the number of buildings studied was very limited and later studies, where more data were available, showed a poor fit. The original buildings studied were also all located in California, and it is questionable if buildings located elsewhere would follow a similar trend (Gilles, 2011). This has been recognized by research, and alternative simplified expressions have been derived based on experimental periods measured in buildings in different regions of the world.…”
Section: Approximate Fundamental Period Formulaementioning
confidence: 98%
See 1 more Smart Citation
“…The problem lies in the fact that the number of buildings studied was very limited and later studies, where more data were available, showed a poor fit. The original buildings studied were also all located in California, and it is questionable if buildings located elsewhere would follow a similar trend (Gilles, 2011). This has been recognized by research, and alternative simplified expressions have been derived based on experimental periods measured in buildings in different regions of the world.…”
Section: Approximate Fundamental Period Formulaementioning
confidence: 98%
“…Following the same procedure as in Gilles (2011), multiple linear regressions were performed on the data sets for C2 and C3 buildings to explore how expressions of the type fit the measured data, where is the measured fundamental period and is the height of the building above ground, in meters. Three cases were considered based on the allowed values for the exponent .…”
Section: Figure 4 Experimental Data and Nbc Formula For Concrete Shementioning
confidence: 99%
“…Further, a significant inconsistency can be observed in eq. [5] when some shear walls do not extend to the top of a building (Gilles 2011). …”
Section: Goel and Chopra Fundamental Period Formulamentioning
confidence: 99%
“…Below is a brief description of the data collection and analysis procedures, which are described in more detail in Gilles (2011) and . For each building, velocities resulting from ambient excitations were recorded at several locations, distributed spatially along the height and plan dimensions, using two Lennartz LE-3D/5s tri-axial seismometers (Lennartz Electronic 2011).…”
Section: Natural Period Datamentioning
confidence: 99%
“…The code period formula used to calculate the building's fundamental period has been evaluated by several researchers (Goel and Chopra 1998;Lee et al, 2000;Morales, 2000;Gilles, 2011) for its applicability to concrete shear wall buildings. Only one study proposed an alternative period equation for wood based buildings (Camelo, 2003), which presents a clear need to evaluate the code period equation, using a comprehensive data base of natural periods from real buildings.…”
Section: Summary Of Literature Review 23mentioning
confidence: 99%